KAJIAN NILAI-NILAI AJARAN BUDDHA SEBAGAI LANDASAN ETIKA BISNIS - Andhika Mustika Dharma; Dika Arya Yasa; Mulyana (Pascasarjana Universitas Hindu Indonesia, 2026)
This study is a continuation of previous research that examined Buddhist teachings in the Aṅguttara Nikāya related to business ethics. The present study aims to analyze Buddhist values more broadly as a foundation for business ethics, focusing on Buddhist teachings without being limited to a single Nikāya. Although Buddhist teachings predominantly address liberation (nibbāna) and mental discipline, they also contain ethical principles that are relevant to economic and business activities, particularly in the context of achieving well-being without causing suffering. This research employs a literature review method with a qualitative approach and adopts a descriptive-analytical research design. The primary data source is the Tipiṭaka, supported by scholarly articles, books, and other relevant sources on business ethics. Data analysis was conducted through several stages: data collection, data reduction, thematic categorization of values, interpretation of meaning, and drawing conclusions. The findings indicate that business ethics from a Buddhist perspective emphasize honesty and the principle of not causing harm to oneself or others. They also stress awareness of limitations in profit-seeking and resource utilization, as well as the practice of right speech, right thought, and right action. Furthermore, Buddhist teachings encourage business actors to adopt a realistic attitude, focus on practical implementation, and view experiences of loss as opportunities for learning rather than regret. These values can serve as an ethical framework for developing sustainable business practices oriented toward collective well being.